PERBEDAAN PERSEPSI KARYAWAN BERDASARKAN JENIS KELAMIN TERHADAP TIPE KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL (STUDI PADA PT INDOFOOD SUKSES MAKMUR SEMARANG) - Silaya, Micrets Agustina (P3M- Politeknik Negeri Kupang, 2016)
Today’s life is no longer featured by simplicity as past times, rather it is filled by diversitiesand changes of new way of thinking. Leadership practices based on past theories are no longerable in creating a more fundamental change and what is more needed today is change of behavior,values, and motivation. This fundamental change is essential due to their increasing needs. Inorder to respond those needs, thus a kind of leadership theory was developed that is known astransactional and transformational leadership.In addition to leader, employees have their own important role in running the life oforganization’s business and become active players in every organization’s activities. As we knowthat in general from since birth, men and women are treated differen.Those differences and characteristics will be brought into the working world, and by thepresence of those differences indeed will cause different employee’s perception (point of view)with others, even though they are put together in a same work environment.Therefore, this research has an objective to analyze difference in perception based on genderrelated to transactional and transformational leadership. Research sample was 98 employees ofPT. Indofood Sukses Makmur. Data was collected through questionnaire dissemination. Researchresults showed that there was no difference in perception based on gender.